Metabolic engineering of Bacillus amyloliquefaciens for enhanced production of S-adenosylmethionine by coupling of an engineered S-adenosylmethionine pathway and the tricarboxylic acid cycle - Ruan, Liying (Biotechnol Biofuels, 2019)
BACKGROUND: S-Adenosylmethionine (SAM) is a critical cofactor involved in many biochemical reactions. However, the low fermentation titer of SAM in methionine-free medium hampers commercial-scale production. The SAM synthesis pathway is specially related to the tricarboxylic acid (TCA) cycle in Bacillus amyloliquefaciens. Therefore, the SAM synthesis pathway was engineered and coupled with the TCA cycle in B. amyloliquefaciens to improve SAM production in methionine-free medium. RESULTS: Four genes were found to significantly affect SAM production, including SAM2 from Saccharomyces cerevisiae, metA and metB from Escherichia coli, and native mccA. These four genes were combined to engineer the SAM pathway, resulting in a 1.42-fold increase in SAM titer using recombinant strain HSAM1. The engineered SAM pathway was subsequently coupled with the TCA cycle through deletion of succinyl-CoA synthetase gene sucC, and the resulted HSAM2 mutant produced a maximum SAM titer of 107.47 mg/L, representing a 0.59-fold increase over HSAM1. Expression of SAM2 in this strain via a recombinant plasmid resulted in strain HSAM3 that produced 648.99 mg/L SAM following semi-continuous flask batch fermentation, a much higher yield than previously reported for methionine-free medium. CONCLUSIONS: This study reports an efficient strategy for improving SAM production that can also be applied for generation of SAM cofactors supporting group transfer reactions, which could benefit metabolic engineering, chemical biology and synthetic biology.